Use of platelet-rich plasma isolated or in combination in osteoarthritis of the temporomandibular joint: a systematic review - Santos, Paulo Cesar dos (2024)
Introduction: Temporomandibular joint osteoarthritis (TMJ-OA) is a common disease in the oral and maxillofacial regions and is the most serious type. Among temporomandibular disorders, TMJ-OA accounts for 18% to 85% of all cases. The use of platelet-rich plasma (PRP) has been highlighted, as well as in combination with other types of treatments such as hyaluronic acid, arthrocentesis, and corticosteroids. Objective: to highlight the main clinical outcomes of the treatment of osteoarthritis of the temporomandibular joint through the injectable use of platelet-rich plasma, alone or in combination with other types of treatment. Methods: The research and development of the work were carried out from December 2023 to February 2024 in the databases Scopus, PubMed, Science Direct, and Scielo, using scientific articles from 2013 to 2023, following the PRISMA rules. The quality of the studies was based on the GRADE instrument and the risk of bias was based on the Cochrane instrument (Funnel Plot). Results and Conclusion: A total of 178 studies were found that were subjected to eligibility analysis. The final sample had 45 eligible studies and 31 studies were described in the systematic review. Most studies showed homogeneity in their results, with X2 =66.7% >50%, with p<0.05. The symmetric funnel plot did not suggest a risk of bias among studies with a small sample size. The results showed that platelet-rich plasma performed better than hyaluronic acid in the treatment of osteoarthritis of the temporomandibular joint during longterm follow-up in terms of reducing pain and increasing interincisal distance. Combined injection of hyaluronic acid and platelet-rich plasma after arthrocentesis is more effective than hyaluronic acid or platelet-rich plasma alone in the treatment of osteoarthritis of the temporomandibular joint, as well as platelet-rich plasma with hyaluronic acid after arthrocentesis showed significant clinical efficacy long-term concerning pain relief. Furthermore, it was found that intra-articular injections of platelet-rich plasma reduced pain on palpation of the temporomandibular joint more effectively compared to hyaluronic acid and corticosteroids. Platelet-rich plasma injection can significantly improve pain, mouth opening, abnormal joint sound, and jaw function in patients with temporomandibular joint osteoarthritis, and has a good repair effect on condylar bone defects. Furthermore, platelet-rich plasma injection combined with physical therapy can effectively control medium and long-term pain in patients.